Reality in the Margins, Pseudo-Reality in the Main Frame: The Posthuman in Steven Hall’s "The Raw Shark Texts" - Guenther, Shawna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2019)
I contend that, at its core, Stephen Hall’s The Raw Shark Texts is an allegory of reading that illustrates how composite realities exist in the increasingly electronically-dominated world of posthumanism. Hall succinctly identifies how words act upon readers intellectually and psychologically. Readers take the written words from the page and turn them into actual people, places, things, and events within their minds, bringing their own past narratives to create their versions of the text’s pseudoreality. However, the text’s main character, Eric, is disabled by his repeated episodes of complete amnesia – his reality is constantly being erased and rewritten, just like computer memory, leaving Eric with no past narrative to inform his present and future. Hall, very much aware of the conflict between reality and pseudoreality, conflates the worlds of written and digital text, and of human and computer memory in ways that both celebrate their coexistence and warn of one’s potential to eliminate the other. Thus, the allegory of reading exemplifies the potential destruction of reading and the end of electronic posthumanism. As digital text and the mainframe threaten to destroy the act of reading in the twenty-first century, the death of the reader looms large.